Cultural Da‘wah and Public Policy in Urban Prostitution Management: A Case Study of the Closure of Dolly in Surabaya - Priyanto, Agung; Sutriyono (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This study examines a new model for addressing urban prostitution through a collaborative framework that integrates cultural da'wah and public policy, using the closure of Dolly District as a case study. Employing a descriptive qualitative method based on literature analysis and policy documents, the research traces patterns of interaction between culturally grounded religious approaches and governmental interventions. The findings suggest that cultural da'wah plays a significant role in shaping the community's moral awareness, while public policy facilitates the necessary structural changes. Their collaboration generates a more effective mechanism of social transformation compared with administrative closure alone. The study concludes that the synergy between cultural da'wah and public policy offers a new paradigm for tackling prostitution: one that goes beyond shutting down localisation sites by fostering a humane and sustainable social transition. This model has the potential to be replicated in similar urban contexts.